Human Cytomegalovirus Infection as a Risk Factor for Type 2 Diabetes Mellitus Development in a Sample of Iraqi Patients (Medico Legal Update, 2021)
Type 2 diabetes mellitus which abbreviate as T2DM is a complex endocrine and metabolic disorder arisingfrom genetic and environmental factors interaction which in turn induce various degrees of insulin functionalalteration on peripheral tissues. Globally, T2DM has develop into a public health problem. Therefore, Thestudy included (75) patients(37 female and 38 males) suffering from T2DM who visit al-kadhimiya teachinghospital with age range 20-80 years and (70) as healthy controls with age range 20-70 years. All studiedgroups were evaluated CMV IgG by ELISA,B. urea, S. Creatinine, cholesterol and triglyceride the resultsshowed that B.urea, S.creatinine and serum cholesterol showed a non-significant differences between studiedgroup, While there was significant differences in concentration of triglyceride between both studied group.The seropositivity of CMV IgG was 62(82.87%) in T2DM patients with significant differences in compareto control.